2011
DOI: 10.2214/ajr.10.5584
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer: Correlation of Apparent Diffusion Coefficient With Tumor Grade, Depth of Myometrial Invasion, and Presence of Lymph Node Metastases

Abstract: ADC values allow normal endometrium to be differentiated from endometrial carcinoma; however, they do not correlate with histologic tumor grade, the depth of myometrial invasion, or whether lymph node metastases are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
75
3
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 26 publications
21
75
3
4
Order By: Relevance
“…In patients with endometrial cancer, DWI has shown promising results (8,27,28) for prediction of deep myometrial invasion, but discordant results have been reported for prediction of tumor grade (29)(30)(31). Most studies (29)(30)(31) have been focused on selected regions of interest (ROIs) placed on a representative image of the tumor for analysis.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with endometrial cancer, DWI has shown promising results (8,27,28) for prediction of deep myometrial invasion, but discordant results have been reported for prediction of tumor grade (29)(30)(31). Most studies (29)(30)(31) have been focused on selected regions of interest (ROIs) placed on a representative image of the tumor for analysis.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Most studies (29)(30)(31) have been focused on selected regions of interest (ROIs) placed on a representative image of the tumor for analysis. Thus, these techniques do not allow assessment of the problems of ROI size and positioning variations.…”
Section: Author Contributionsmentioning
confidence: 99%
“…DWI, as a functional MRI technique, provides non-invasive and high-resolution information on tissue characteristics based on molecular water diffusion properties, and the imaging output is useful to determine tissue microstructure, density, microcirculation and cellular organization (9,11,33). Several studies describe a close association between cell density and ADC values (16,(33)(34)(35). High ADC values are present in benign lesions, including primary neoplasms that contain low cell densities, while low ADC values are typically observed in malignant neoplasms, due to high cell densities and altered membrane permeability (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The temporal and spatial resolutions of FLASH-3D are also enhanced. 4,10,11 In addition to the speed of imaging, the high signal-to-noise ratio aids the detection of small lesions and early endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FLASH-3D is also able to detect signal foci or small lesions on T2WI, thus providing clearer information for the early diagnosis of muscular invasion, and cervical and lymph node metastases in patients with endometrial carcinoma. [11][12][13] Based on the detection of endometrial damage, junctional zone disruption and the extent of myometrial invasion, FLASH-3D can assess the degree of tumour infiltration and FIGO staging, which have great clinical significance.…”
Section: Discussionmentioning
confidence: 99%